1988
DOI: 10.1159/000138400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cilostazol, a Selective cAMP Phosphodiesterase Inhibitor on the Contraction of Vascular Smooth Muscle

Abstract: The effects of cilostazol (OPC-13013, 6-[4-(1-cyclohexyl-1H-tetrazol-5-yl)butoxy]-3,4-dihydro-2(1H)-quinolinone) on cyclic nucleotide metabolism and Ca2+-induced contraction of intact and skinned rabbit arterial smooth muscles were investigated. The concentrations of cilostazol producing 50% inhibition of cyclic adenosine monophosphate phosphodiesterase and Ca2+-dependent cyclic nucleotide phosphodiesterase were 0.4 μM and above 100 μM, respectively. This compound has no significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 9 publications
1
93
0
1
Order By: Relevance
“…Cilostazol has been shown to induce vasodilation via increasing cyclic adenosine monophosphate (cAMP) rather than nitric oxide release. [25][26][27][28] A preliminary study showed that cutaneous blood perfusion in response to cilostazol was maximally increased at 15 to 20 minutes in mice. The procedure was the same as before except 2 measurements were performed 15 minutes after topical administration of 1% cilostazol and averaged.…”
Section: Assessments Of Cutaneous Blood Perfusion By a Laser Doppler mentioning
confidence: 99%
See 1 more Smart Citation
“…Cilostazol has been shown to induce vasodilation via increasing cyclic adenosine monophosphate (cAMP) rather than nitric oxide release. [25][26][27][28] A preliminary study showed that cutaneous blood perfusion in response to cilostazol was maximally increased at 15 to 20 minutes in mice. The procedure was the same as before except 2 measurements were performed 15 minutes after topical administration of 1% cilostazol and averaged.…”
Section: Assessments Of Cutaneous Blood Perfusion By a Laser Doppler mentioning
confidence: 99%
“…Consistent with this hypothesis, a parallel experiment using cilostazol, a selective cAMP phosphodiesterase inhibitor that has been shown to increase blood flow in the skin after topical administration, 25 showed no difference in the blood flow response between the 2 groups at 7.5 months of age. Cilostazol blocks cAMP hydrolysis, elevates vascular smooth muscle cell cAMP levels, and produces vasodilation in vitro and in vivo 26,27 with no effect on nitric oxide production. 28 These results observed in Apoe -/-mice showed a deficit of nitric oxide-mediated vasodilation associated with extensive atherosclerosis and elevated blood pressure, which is consistent with endothelial dysfunction.…”
Section: Apoementioning
confidence: 99%
“…Nobiletin has been reported to show inhibitory effects against cAMP phosphodiesterase and possess an inhibitory effect on histamine release from peritoneal mast cells (6,7). In addition, in the case of smooth muscle, it has been proposed that the inhibition of cAMP phosphodiesterase is closely related to the relax ation of smooth muscle (38). Hence, the relaxatory effect of nobiletin on smooth muscle may be due to the inhibi tion of cAMP phosphodiesterase.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In a 12-week, double-blind clinical trial in patients with intermittent claudication, initial claudication distance and absolute claudication distance were significantly improved by 35% and 41%, respectively, in the participants who received cilostazol 100 mg twice daily (n = 52) compared with participants who received placebo (n = 25) (P < 0.01). [5] In a 24-week, double-blind clinical trial in patients with peripheral arterial disease, absolute claudication distance was significantly improved by 54% in the participants who received cilostazol 100 mg twice daily (n = 227) compared with participants who received pentoxifylline (n = 232) (P < 0.001).…”
Section: Transl Clin Pharmacolmentioning
confidence: 97%